2004
DOI: 10.1164/rccm.200406-754oc
|View full text |Cite
|
Sign up to set email alerts
|

Associated Loss of Fat-free Mass and Bone Mineral Density in Chronic Obstructive Pulmonary Disease

Abstract: We hypothesized that in patients with chronic obstructive pulmonary disease, loss of fat-free mass (FFM) and loss of bone mineral density (BMD) were related to (1) each other and may be clinically inapparent, (2) urinary markers of cellular and bone collagen protein breakdown, and (3) severity of lung disease. Eight-one patients and 38 healthy subjects underwent dual-energy X-ray absorptiometry to determine body composition and BMD. Urinary protein breakdown markers, inflammatory mediators, and their soluble r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
228
0
20

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(265 citation statements)
references
References 57 publications
15
228
0
20
Order By: Relevance
“…COPD and bronchial asthma are risk factors for osteoporosis; these patients often display a loss of significant amounts of both cortical and trabecular bone [1][2][3][4][5][6][7][8][9]. These patients are also often treated with oral or inhaled glucocorticoids and this contributes to significant additional bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD and bronchial asthma are risk factors for osteoporosis; these patients often display a loss of significant amounts of both cortical and trabecular bone [1][2][3][4][5][6][7][8][9]. These patients are also often treated with oral or inhaled glucocorticoids and this contributes to significant additional bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…the prevalence of reduced bone density and vertebral fractures in patients with chronic obstructive pulmonary disease (COPD) is high [1][2][3][4]; furthermore case-control studies have confirmed reduced bone mineral density (BMD) in COPD patients compared with controls [5][6], even in those with milder disease [7] while in patients who have osteoporosis and spinal deformities, reduced pulmonary function is related to the severity of osteoporosis [9][10][11] in the same way that the worse the level of lung function in COPD patients, the greater the likelihood of low BMD [12].…”
Section: Introductionmentioning
confidence: 99%
“…Low BMD is correlated with reduced FFM in COPD patients [125]. However, COPD itself may be a risk factor for osteoporosis and this may be related to systemic inflammation.…”
Section: Osteoporosismentioning
confidence: 94%
“…Furthermore, fat mass may be redistributed from subcutaneous to visceral adipose tissue, which has been associated with increased cardiovascular risk in mild to moderate COPD [20]. COPD patients with underweight or low FFM are more prone to loss of BMD than overweight patients [21]. DEXA is most appropriate for combined screening of osteoporosis, FFM and fat mass.…”
Section: Metabolic Phenotypes and Nutritional Risk Profile In Copdmentioning
confidence: 99%